2022
DOI: 10.1177/1071181322661367
|View full text |Cite
|
Sign up to set email alerts
|

Do Drivers Respond to Lead Vehicles Gradually or Suddenly?

Abstract: The aim of the current study was to determine whether drivers’ responses to stopped and slow-moving lead vehicles transition gradually in phases, each associated with a distinct optical expansion rate. We also examined whether results were affected by a cell phone conversation and expectancy. We used a driving simulator to assess six response inputs of (1) begins to release the accelerator, (2) releases accelerator completely, (3) starts to press brake (4) comfort-level braking (5) unanticipated-level braking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Prior research suggests that drivers will not respond to a lead vehicle until they perceive it as an immediate hazard— when the optical expansion rate reaches 0.006 rad/s (Muttart et al, 2005). However, our recent driving simulator study showed that, with daytime scenes, drivers responded gradually in phases rather than suddenly to stopped lead vehicles before reaching this threshold (Oliver et al, 2022). Here we examined whether this same pattern of results would occur in nighttime scenes.…”
mentioning
confidence: 99%
“…Prior research suggests that drivers will not respond to a lead vehicle until they perceive it as an immediate hazard— when the optical expansion rate reaches 0.006 rad/s (Muttart et al, 2005). However, our recent driving simulator study showed that, with daytime scenes, drivers responded gradually in phases rather than suddenly to stopped lead vehicles before reaching this threshold (Oliver et al, 2022). Here we examined whether this same pattern of results would occur in nighttime scenes.…”
mentioning
confidence: 99%